Development of Character-Based Student Worksheets in Online Learning in Geography Subjects - Anugrah Isromi; Abdul Malik; Rosmini Maru (STAI Hubbulwathan Duri, 2022)
This research is a Research and Development which aims to develop and determine the feasibility of character-based student worksheets in the subject of Geography. The development model applied is a 4-D model which is modified into 3-D consisting of define, design, and develop. Data collection techniques were carried out using observation, interviews, documentation, and questionnaires. The results of research and development show that first, character-based student worksheets have been able to be developed and declared very valid based on the results of the questionnaire obtained from the assessment and responses by validators, namely material experts at 90.52 %, linguistic experts at 95.00 %, and teaching materials experts at 84.00 %. Second, character-based worksheets are considered very practical based on the results of the teacher's response questionnaire of 91.30 % and students of 86.60 %. The character-based student worksheets that have been produced have only been tested on a limited group, so it is necessary to conduct extensive trials in order to further confirm the effectiveness of the student worksheets made. In addition, the character-based student worksheets produced is only limited to one Basic Competence, therefore further development can be carried out with other Basic Competencies so that the process of strengthening character values can be carried out more deeply.